2018
DOI: 10.5395/rde.2018.43.e18
|View full text |Cite
|
Sign up to set email alerts
|

Retention of BioAggregate and MTA as coronal plugs after intracanal medication for regenerative endodontic procedures: an ex vivo study

Abstract: ObjectivesThis study compared the retention of BioAggregate (BA; Innovative BioCeramix) and mineral trioxide aggregate (MTA; Angelus) as coronal plugs after applying different intracanal medications (ICMs) used in regenerative endodontics.Materials and MethodsOne-hundred human maxillary central incisors were used. The canals were enlarged to a diameter of 1.7 mm. Specimens were divided into 5 groups (n = 20) according to the ICM used: calcium hydroxide (CH), 2% chlorhexidine (CHX), triple-antibiotic paste (TAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 50 publications
2
9
1
2
Order By: Relevance
“…In the present study, Ca(OH) 2 had the highest bond strength compared with the typical clinical concentration of TAP and DAP as well as to the control regardless of the cement type. Previous studies generally agreed with the present findings for MTA 32,33 and Endosequence putty. 34 However, other studies showed no effects on the bond strength of MTA 12,28 and Biodentine 28 when Ca(OH) 2 was used.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, Ca(OH) 2 had the highest bond strength compared with the typical clinical concentration of TAP and DAP as well as to the control regardless of the cement type. Previous studies generally agreed with the present findings for MTA 32,33 and Endosequence putty. 34 However, other studies showed no effects on the bond strength of MTA 12,28 and Biodentine 28 when Ca(OH) 2 was used.…”
Section: Discussionsupporting
confidence: 93%
“…31,33,34,43 Contrary to the current study, no predominant failure mode was reported when 1,000 mg/mL DAP was used with the three cements types. 10,31,33,34 One study reported a predominant adhesive failure with 1,000 mg/mL DAP for MTA cement. 31…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…MTA retention, as an ideal restorative coronal sealing material after REP, is best with the use of non-setting calcium hydroxide as an intracanal medicament 40…”
Section: Discussionmentioning
confidence: 99%